Female Action Hero’s Superpower Representation: Audience Reception on Twitter in Disney’s Mulan (2020) - Winda Nur Pratiwi; Fitria Akhmerti Primasita (Universitas Gadjah Mada, 2022)
The live-action adaptation of the Movie Mulan produced by Walt Disney in 2020 sparked heated discussion from the audience after Disney tries to represent a strong female action hero by giving Mulan, the female protagonist, a superpower attribute called ‘chi’. In the era of new media, audience expressed their opinion through Twitter. Thus, the tweet responses and reviews on several websites were consecutively taken as primary and secondary data as it is an audience analysis research, applying feminist theory to examine the audience responses to the representation of female action heroes with a superpower. The research found that the majority of the audience, approximately 80%, falls into the opposition audience. They do not like the representation of Mulan with a superpower. On the other hand, less than 20% of audience fall into the dominant and negotiate audience. The high percentage of the oppositional audience indicates that the audience of the live-action Mulan would rather choose the representation of Mulan who came from a humble background instead of someone who was born great.